App Nortear: protótipo de aplicativo educacional como apoio ao docente que atua com discente com Transtorno do Espectro do Autismo no Ensino Superior - FERREIRA, Juliene de Sousa (Universidade Federal do Pará, 2024)
The right to academic inclusion of Autism Spectrum Disorder (ASD) students is provided in Brazilian state policies and legislation. Its implementation, and the increase of students with ASD enrolled in Higher Education, as a result, the educational scenario has changed. This student faces several adaptation obstacles due to their specific needs and teachers have difficulties in dealing with these students in the classroom. In these terms, the objective of this research was to develop an educational mobile application prototype (app) to support teaching practices in the classroom with students with ASD in Higher Education. This is an applied research, field survey, quantitative and qualitative, using semi-structured interviews, with teachers who have already had experience with students with ASD in Higher Education and an online questionnaire with the multidisciplinary team of the Accessibility and Inclusion Centers (NAI ) from UFRA and UFPA. Among the central authors of this research are: Tardif (2014), who understands that knowledge is acquired from personal experiences; Pimenta, Anastasiou and Cavallet (2003), who study teaching in Higher Education presupposing reflection and evaluation of practices; Kenski (2012) and Moran (2015), who argue that education can be mediated by technology and Pressman (2016) who states that an app provides support to users in solving problems. The study was also supported by official documents and legislation regarding ASD. To develop the app prototype, we used the evolutionary process model with prototyping as a methodological reference with the main steps: gathering requirements; agile planning; project modeling; prototype development; validation from eight specialist judges in Special Education and feedback on functions. The application named APP NORTEAR was developed using the Figma, Kodular platforms version: 1.5B.3 - Fenix, Canva, Draw.io and Trello. A high-fidelity prototype was developed, with the following contents: Understanding ASD, suggestions for pedagogical practices, relevant guidelines and Accessibility and Inclusion Centers. Based on the evaluations of the expert judges, it was possible to validate the content, functionality and usability of the app. In the judges' assessment, important suggestions were made and will allow the development of new versions. The evaluation results allow us to affirm that the developed application prototype has the potential to support the practice of teachers without training in academic inclusion to work with students with ASD.